Epidemiology of taeniosis/cysticercosis in Europe, a systematic review: eastern Europe - Trevisan, Chiara; Sotiraki, Smaragda; Laranjo-González, Minerva; Dermauw, Veronique; Wang, Ziqi; Kärssin, Age; Cvetkovikj, Aleksandar; Winkler, Andrea S; Abraham, Annette; Bobić, Branko; Lassen, Brian; Cretu, Carmen Michaela; et al. (Springer Nature, 2018)
Taenia solium and Taenia saginata are food-borne parasites of global importance. In eastern Europe only fragmented information is available on the epidemiology of these zoonotic parasites in humans and animal populations. In particular for T. solium, on-going transmission is suspected. The aim of this systematic review was to collect the available data and describe the current knowledge on the epidemiology of T. solium and T. saginata in eastern Europe.
Keywords: Taenia solium; Taenia saginat; Epidemiology; Bovine; Neurocysticercosis; Eastern Europe; Porcine